2012
DOI: 10.1364/josab.29.000559
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian tools for the analysis of optical polarization control

Abstract: The study of the polarization dynamics of two counterpropagating beams in optical fibers has recently been the subject of a growing renewed interest, from both the theoretical and experimental points of view. This system exhibits a phenomenon of polarization attraction, which can be used to achieve a complete polarization of an initially unpolarized signal beam, almost without any loss of energy. Along the same way, an arbitrary polarization state of the signal beam can be controlled and converted into any oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Note that the finite size of the SOP spot can also be interpreted theoretically by the fact that the singularities lie on the boundary of the energy-momentum diagram (see Fig. 2 of the supplementary materials), so that convergence to the singularities cannot take place in an isotropic way, which limits the efficiency of the attraction process27. We remark that the polarization controller inserted into the reflective loop of Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Note that the finite size of the SOP spot can also be interpreted theoretically by the fact that the singularities lie on the boundary of the energy-momentum diagram (see Fig. 2 of the supplementary materials), so that convergence to the singularities cannot take place in an isotropic way, which limits the efficiency of the attraction process27. We remark that the polarization controller inserted into the reflective loop of Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The role of such stationary states has already been discussed in different works for the analysis of the conventional process of polarization attraction involving two injected beams [14][15][16]. It was shown that such systems exhibit Hamiltonian singularities, which play the role of attractors for the spatiotemporal dynamics [17].…”
Section: Theoretical Descriptionmentioning
confidence: 97%
“…As opposed to traditional polarizers, which are known to waste 50% of unpolarized light, Heebner et al proposed in 2000 a "universal polarizer" performing repolarization of unpolarized light with 100% efficiency [1]. Subsequently, this phenomenon of polarization attraction or polarization pulling has been the subject of growing interest in optical fiber systems, involving the Raman effect [2][3][4], Brillouin backscattering [5,6], parametric amplification [7,8], and the full-degenerate four-wave mixing process, also called cross-polarization rotation [9][10][11][12][13][14][15][16][17][18][19]. Note that, from a broader perspective, the recent works obtained in a counterpropagating configuration in telecommunication fibers are inherently based on a four-wave interaction, which has been the subject of pioneering studies in the past [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of a relatively simple deterministic model for describing nonlinear lossless polarizers based on randomly birefringent telecom fibers provides a key tool for numerically estimating their performance. Moreover, the properties of steady-state solutions of the averaged polarization evolution equations may be described in terms of mathematical techniques developed for the study of Hamiltonian singularities [30]. Such approach has led to the interesting observation that polarization attraction is closely linked with the existence of singular tori or multidimensional separatrix solutions [31][32][33].…”
Section: B Theory Of Lossless Polarizersmentioning
confidence: 99%